Transcatheter Treatment of Liver Laceration from Blunt Trauma - Hardy, Andrew Hal; Phan, Ho; Khanna, Pavan; Nolan, Timothy; Dong, Paul (Seminars in Interventional Radiology, 2012)
Blunt hepatic trauma is a fairly common pathology seen in trauma centers. We describe a pediatric patient who suffered blunt hepatic trauma that was managed successfully with a combination of exploratory laparotomy and liver packing, followed by hepatic artery embolization by interventional radiology (IR) after he continued to have significant arterial extravasation. Also discussed are trends in overall blunt hepatic trauma management and the technique of IR management.
Keywords: blunt hepatic trauma; liver active extravasation; hepatic artery embolization; interventional radiology